Collaborative Research Training Based on Virtual Spaces - Rodríguez, Darío (2010)
A possible strategy for training researchers is to provide integrated research cores with researchers-in-training under the guidance of a senior trained researcher. Information technology and communication have enabled the construction of virtual communities formed by individuals who may be far away physically but who are cognitively close, hence giving rise to collaborative research training models. In this context, this paper formulates an approach to identify the elements of the work space of a research group devoted to research training and to assess the technological feasibility of virtualization of such elements.